2014
DOI: 10.1111/cen.12429
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study of hyponatraemia as an independent risk factor for inpatient mortality

Abstract: This study showed that hyponatraemia is an independent predictor of mortality, and hyponatraemia per se is likely to contribute to excess mortality. Further studies are needed to examine whether correction of hyponatraemia can reduce mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 30 publications
1
44
2
3
Order By: Relevance
“…Given that reported mortality rates vary according to the cutoff point used to define HN, it is difficult to compare the mortality rates observed in our study to the rates described by other authors. Patients with SNa levels ranging from 128 to 138 mmol/L reported mortality rates ranging from 3.4 to 17.3% [3,6,7,10]. In contrast with other studies, we found no significant association between HN and mortality in the PNG after adjusting for confounding factors.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Given that reported mortality rates vary according to the cutoff point used to define HN, it is difficult to compare the mortality rates observed in our study to the rates described by other authors. Patients with SNa levels ranging from 128 to 138 mmol/L reported mortality rates ranging from 3.4 to 17.3% [3,6,7,10]. In contrast with other studies, we found no significant association between HN and mortality in the PNG after adjusting for confounding factors.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we found that the mortality rate in patients with sustained HN (75% of all intraindividual SNa measurements < 135 mmol/L) was up to 7 times greater than that in patients without HN, and independent of age, gender, CCI, or BMI. This finding is of interest given that, to date, none of the studies that have examined mortality rates in hyponatremic patients [3,6,7,8,9,10] have analyzed the effect of sustained HN versus single SNa values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, our case further highlighted the contrarian observation that with a high index of suspicion for CSW and its early diagnosis, volume depletion and hypovolemia from polyuria may not be a distinguishing presenting factor, when contrasted with SIADH (7-9). Moderate to severe hyponatremia is acknowledged to increase inpatient mortality (12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%